The Effect of Predicting Strategy for Listening Comprehension in EFL Classroom on the Third Year Students (academic year 2012) at English Department in FKIP Universitas HKBP Nommensen Pematangsiantar - Bobby P. S. Dhillon; Bertaria Sohnata Hutauruk (Universitas Bunda Mulia, 2017)
This research will tend to find out the significance and the effect predicting strategy for Listening Comprehension in EFL classroom on the third year students (Academic Year 2012) at English Department in FKIP Universitas HKBP Nommensen Pematangsiantar. This research will use experimental research design. To answer the problems of the research, the writer uses the following theories: Nunan (2003), Ellis & Sinclair (1997), Rost (1999), Miller (2000:25), Richards and Rodgers (1986:16), Anthony (1963:15), Buck (1999), Flowerdew (1994), Swain (2000), Chamot (1999;15), Anderson and Lynch (1988), Harmer(1983), and Tiwari (2005). The population of this research is the third year students (Academic Year 2012) at English Department that sit in Listening Comprehension in FKIP Universitas HKBP Nommensen Pematangsiantar. There are 90 students taken as the sample of this research. The sample was divided into two groups: the first group (30 students) as the experimental group and the second group (30 students) as the control group. The writers will give a treatment in the class by using predicting strategy in teaching listening comprehension. The data obtained from the score of experimental group and the score of the control group were calculated by applying t-test formula. (1) the result shows that t-observed > t-table = 6.13 > 2.00 (p=0.05; df=58). It indicates that Prediction strategy gave significant effect to the students’ listening comprehension. The students who were taught by using Prediction Strategy got higher score than those who were taught without using Prediction Strategy, (2) Teaching listening by using Prediction Strategy makes the students become active listeners and give them a better chance of general comprehension. While, the common situation found in the classroom shows that teacher often test listening skill rather than teach it. It makes listening class be passive and the students are not motivated (3) The difference of the mean scores in the pre-test and post-test of both experimental and control group were calculated by using t-test formula to find t-observed. T-test formula was used to assess whether the means score of experimental group and control group are different from each other, (4) From the calculation, it is found that t-observed (6,13) is higher than t-table (2.00). Thus, alternative hypothesis (Ha) is accepted. Keywords: predicting strategy, listening comprehension, teaching